Câu 1:
a) \( A=\sqrt{18}-\sqrt{(1-\sqrt{2})^{2}}-1 \)
Giải thích:
\[ A = \sqrt{18} - |1-\sqrt{2}| - 1 \]
\[ A = \sqrt{18} - (1-\sqrt{2}) - 1 \]
\[ A = \sqrt{18} - 1 + \sqrt{2} - 1 \]
\[ A = 2\sqrt{2} - 2 \]
b) \( B=(1-\sqrt{5}) \frac{5+\sqrt{5}}{2 \sqrt{5}} \)
Giải thích:
\[ B = (1-\sqrt{5}) \cdot \frac{5+\sqrt{5}}{2\sqrt{5}} \]
\[ B = \frac{(1-\sqrt{5})(5+\sqrt{5})}{2\sqrt{5}} \]
\[ B = \frac{5 - \sqrt{5} - 5\sqrt{5} + 5}{2\sqrt{5}} \]
\[ B = \frac{-4\sqrt{5}}{2\sqrt{5}} \]
\[ B = -2 \]
c) \( C=\left(\frac{\sqrt{x}}{x+2 \sqrt{x}}+\frac{1}{\sqrt{x}-2}\right) \cdot\left(1+\frac{2}{\sqrt{x}}\right) \quad(x>0, x \neq 4) \)
Giải thích:
\[ C = \left(\frac{\sqrt{x}}{x+2\sqrt{x}} + \frac{1}{\sqrt{x}-2}\right) \cdot \left(1 + \frac{2}{\sqrt{x}}\right) \]
\[ C = \left(\frac{\sqrt{x}}{x+2\sqrt{x}} + \frac{1}{\sqrt{x}-2}\right) \cdot \left(\frac{\sqrt{x}+2}{\sqrt{x}}\right) \]
\[ C = \frac{\sqrt{x}(\sqrt{x}+2)}{x+2\sqrt{x}} + \frac{\sqrt{x}+2}{\sqrt{x}-2} \]
\[ C = \frac{x+2\sqrt{x} + \sqrt{x}+2}{x+2\sqrt{x}} \]
\[ C = \frac{x+3\sqrt{x}+2}{x+2\sqrt{x}} \]